Analisis Debit Andalan dan Kebijakan Pengelolaan Daerah Aliran Sungai Bengkulu untuk Ketersediaan Air Baku Di Kota Bengkulu (Analysis of Dependable Discharge and Management Policy of Bengkulu Watershed for Raw Water Availability in Bengkulu City) - Idham Khalik; Asep Sapei; Sigid Hariyadi; Elisa Anggraeni (Jurnal Penelitian Pengelolaan Daerah Aliran Sungai (Journal of Watershed Management Research), 2025)
Watersheds must be managed as a unified area from upstream to downstream, by considering various geophysical and socio-economic aspects. Changes in watershed morphology are one of the important factors that can affect the hydrological system and affect the water availability of a region. The study aimed to analyse the dependable discharge of the Bengkulu River and develop policies for  sustainable management of the Bengkulu Watershed. The methods used to analyze the reliable discharge are the Weibull distribution flow duration curve (with 90% probability) and Interpretive Structural Modelling (ISM). Results showed that, from 1990 to 2020, land use in the Bengkulu Watershed changed in the form of a 34,58 km2 (7,30%) decrease in Secondary Dryland Forest area, and a 10,54 km2 (2,22%) increase in mining area. The dependable discharge of Bengkulu River (with 90% probability) is 10.93 m3/s or approximately 344.69 million m3. Furthermore, the Bengkulu River’s flow regime coefficient fluctuates considerably and has shows an increasing trend in recent years. This indicates that the watershed is experiencing degradation due to changes in land cover and global climate changes. Some policy recommendations that need to be implemented include integrating spatial planning and watershed management plans across local governments and to guide natural resource management, reforestating or planting trees to maintain vegetated areas, and planting forests and crops through agroforestry.